SWOT Analysis of Business Opportunities in Msmes in Balikpapan City - Indrayani, Indrayani (IJBLE Scientific Publications Community Inc., 2024)
This research uses methods to find out how and strategies to analyse MSME business opportunities in Balikpapan City and how important business opportunity analysis is in entrepreneurship or doing business. Several MSME business opportunities in Balikpapan City that can be chosen, methods and strategies for analysing business opportunities, as well as predicting MSME business opportunity analysis will be discussed. In this way, the public can understand business opportunity analysis, especially SWOT analysis, and can apply it in their respective MSME business ventures. Analysis of business opportunities influences the business that will be run or the one that wants to be developed. This research aims to identify potential MSME business opportunities in Balikpapan City, analyses effective ways and strategies in conducting business opportunity analysis for MSMEs, assess how important business opportunity analysis is in supporting entrepreneurial and business success, introduce and explain the SWOT analysis method as an analytical tool business opportunities, providing guidance to the public regarding the application of business opportunity analysis in developing MSME businesses, as well as evaluating the influence of business opportunity analysis on the success and development of MSMEs in Balikpapan City.